Assessing the industry 4.0 strategies for a steel supply chain: SWOT, game theory, and gap analysis - Sima Motallebi; Mostafa Zandieh; Akbar Alem Tabriz; Erfan Babaee Tirkolaee (Heliyon)
The recent adoption of modern technologies has led to the fourth industrial revolution or Industry 4.0 (I4.0). The supply chain of large industries, such as steel, is of significant importance in the economies of countries. According to data published by the National Iranian Steel Company, the steel industry is one of the most vital sectors in Iran, contributing about 1 % to its Gross Domestic Product (GDP). Therefore, implementing I4.0 in the steel supply chain is a highly significant and practical endeavor, with the potential to drive considerable advancements in this industry. This study develops an efficient integrated framework to identify and evaluate the most critical factors influencing the implementation of I4.0 in the supply chains of large industries. The study also reviews the most effective policies for implementing these factors and analyzes the gap between the current state of the steel supply chain in Iran and the desired state within the framework of I4.0. The components of I4.0 are determined based on a review of existing literature and interviews with experts from the Iranian steel industry, utilizing the fuzzy Delphi method. Afterward, Strengths, Weaknesses, Opportunities, and Threats (SWOT) policies are developed. The optimal combination of policies for implementing I4.0 in the Iranian steel supply chain is identified using game theory. Finally, a gap analysis is conducted between the current state of the industry and the desired state. The critical gap analysis revealed that the current state of the supply chain significantly lags behind the desired I4.0 goals, particularly in terms of infrastructure and supply chain balancing. The findings highlight a stark contrast between the current performance score of 0.16 and the target score of 0.84, underscoring the substantial improvements needed to realize I4.0 within this sector.